Native Language Interference in the spoken target language: A case study of there speakers of english as a foreign language - Quintana Gonzales, Anni Mariela (2011)
To develop my investigation some different methods were used; among them was the Bibliographic method. It was used to gather scientific information through books, magazines, and Internet, in order to do the theoretical frame.